Phosphorolytic degradation of leaf starch via plastidic α-glucan phosphorylase leads to optimized plant growth and water use efficiency over the diel phases of Crassulacean acid metabolism. (22nd March 2021) - Ceusters, Nathalie; Ceusters, Johan; Hurtado-Castano, Natalia; Dever, Louisa V; Boxall, Susanna F; Kneřová, Jana; Waller, Jade L; Rodick, Rebecca; Van den Ende, Wim; Hartwell, James; Borland, Anne M
Abstract : Characterization of RNAi lines of Kalanchoë fedtschenkoi deficient in chloroplastic α-glucan phosphorylase demonstrates that the phosphorolytic route of starch degradation is of central importance for CAM in this model species. Abstract: In plants with Crassulacean acid metabolism (CAM), it has been proposed that the requirement for nocturnal provision of phosphoenolpyruvate as a substrate for CO2 uptake has resulted in a re-routing of chloroplastic starch degradation from the amylolytic route to the phosphorolytic route. To test this hypothesis, we generated and characterized four independent RNAi lines of the obligate CAM species Kalanchoë fedtschenkoi with a >10-fold reduction in transcript abundance of plastidic α-glucan phosphorylase (PHS1). The rPHS1 lines showed diminished nocturnal starch degradation, reduced dark CO2 uptake, a reduction in diel water use efficiency (WUE), and an overall reduction in growth. A re-routing of starch degradation via the hydrolytic/amylolytic pathway was indicated by hyperaccumulation of maltose in all rPHS1 lines. Further examination indicated that whilst operation of the core circadian clock was not compromised, plasticity in modulating net dark CO2 uptake in response to changing photoperiods was curtailed. The data show that phosphorolytic starch degradation is critical for efficient operation of the CAM cycle and for optimizing WUE. This finding has clear relevance for ongoing efforts to engineer CAM into non-CAM species as a means of boosting crop WUE for a warmer, drier future.